Respostas
respondido por:
3
2x+3y=5, x= 5-3y/2, 5( 5-3y)/2 + 2y= 7; 25-15y+4y=14. -11y= -11, y=1. Substitui y p/ achar x, 2x+3.1=5, x=1
respondido por:
5
2x+3y=5 (-5)
5x+2y=7 ( 2)
-10x - 15y = - 25
10x + 4y = 14
- 11y = - 11 (-1)
11y = 11
y = 1
2x+3y=5 ==> 2x + 3.1 = 5 ==> 2x = 5-3 ==> 2x = 2 ==> x = 1
5x+2y=7 ( 2)
-10x - 15y = - 25
10x + 4y = 14
- 11y = - 11 (-1)
11y = 11
y = 1
2x+3y=5 ==> 2x + 3.1 = 5 ==> 2x = 5-3 ==> 2x = 2 ==> x = 1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás